Programmed Cell Death Ligand 1 Is Enriched in Mammary Stem Cells and Promotes Mammary Development and Regeneration - Wang, Ruirui; Huang, Fujing; Wei, Wei; Zhou, Yu; Ye, Zi; Yu, Liya; Hu, Junyuan; Cai, Cheguo (Frontiers in Cell and Developmental Biology, 2021)
PD-L1 is widely expressed in a variety of human tumors, and inhibition of PD-L1/PD-1 pathway represents one of the most promising therapy for many types of cancer. However, the physiological function of PD-L1 in tissue development is still unclear, although PD-L1 mRNA is abundant in many tissues. To address this puzzle, we investigated the function of PD-L1 in mammary gland development. Interestingly, we found that PD-L1 is enriched in Procr-expressing mammary stem cells (MaSCs), and PD-L1-expressing mammary basal cells (PD-L1+ basal cells) exhibit robust mammary regeneration capacity in transplantation assay. Lineage tracing experiment showed that PD-L1+ cells can differentiate into all lineages of mammary epithelium cells, suggesting that PD-L1+ basal cells have the activities of MaSCs. Furthermore, PD-L1 deficiency significantly impairs mammary development and reduces mammary regeneration capacity of mammary basal cells, suggesting that PD-L1 is not only enriched in MaSCs, but also improves activities of MaSCs. In summary, these results demonstrated that PD-L1 is enriched in MaSCs, and promotes mammary gland development and regeneration. Mechanistically, our data indicated that PD-L1 expression is induced by continuous activation of Wnt/ß-catenin signaling. In conclusion, these results demonstrated that PD-L1 is a marker of mammary stem cells, and PD-L1 is essential for mammary development. Our study provides novel insight into the physiological functions of PD-L1 in tissue development.